ENVIRONMENTAL AND ECONOMIC PROBLEMS OF AGROECOSYSTEM UNER AGRICULTURAL INTENSIFICATION IN CONDITIONS OF SOUTHEASTERN KAZAKHSTAN: ENVIRONMENTAL AND ECONOMIC PROBLEMS OF AGROECOSYSTEM UNER AGRICULTURAL INTENSIFICATION IN CONDITIONS OF SOUTHEASTERN KAZAKHSTAN - Suleimenova, Naziya; Filipova, Margarita; Sandugash, Zharaspayeva (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
This article suggests solutions to environmental problems of agro-ecosystem under agricultural intensification, the need to optimize the structure of agro-ecosystem by increasing the portion of highly profitable culture with a good amino acid and protein composition, soybean in particular, improvement of crop rotation with increase of environmentally profitable crops’ portion, that help to restore and improve soil fertility.